2007
DOI: 10.1007/978-3-540-73273-0_17
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Consistent Meshing of Multi-label Datasets

Abstract: Fig. 1. Surface meshes. Left: Meshing the boundaries of brain tissues with a tissue-dependent resolution. We requested the cortical surface (colored in dark gray) to have a resolution twice higher than other tissues. As a result, output surface meshes of other anatomical structures have a coarse resolution except in local regions where they neighbor gray matter. This is apparent in the magnified view of the white matter mesh (in light gray), in which the gray matter interface has been partially removed for vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…The octree techniques [3,4] generate meshes with consistent multi-material junctions, however the quality of the elements at the interfaces turns out to be very poor and needs further improvements. There are methods relying on Delaunay refinement [5,6,7]. In practice, however, even though the quality of the final mesh is good, the representation of the interfaces is not (jiggles).…”
Section: Related Workmentioning
confidence: 98%
“…The octree techniques [3,4] generate meshes with consistent multi-material junctions, however the quality of the elements at the interfaces turns out to be very poor and needs further improvements. There are methods relying on Delaunay refinement [5,6,7]. In practice, however, even though the quality of the final mesh is good, the representation of the interfaces is not (jiggles).…”
Section: Related Workmentioning
confidence: 98%
“…In [13], a lookup table is used in the case of three materials, and in the general case, triangle removal algorithms are used, allowing meshes with boundaries and holes to be created. -Delaunay refinement: These methods are an extension of typical Delaunay refinement-based algorithms to the case of multiple surfaces [14][15][16]. A mesh is iteratively created by adding vertices and updating mesh topology until a quality criteria is reached that terminates the algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…The refinement process is controlled by highly customizable quality and size criteria on triangular facets and on tetrahedra. Pons et al [7] have adapted this mesh generation strategy to labelled images and have shown that the sizing criteria can be tissue-dependent leading to high-quality volume meshes of the different materials. However, in this work, 1-and 0-junctions are not explicitly handled and they are not accurately represented in the output mesh.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, we propose a feature (edge and corner) preserving extension of the Delaunay refinement algorithm introduced by Pons et al [7]. The basic idea is to explicitly sample 1-and 0-junctions before launching the Delaunay refinement and to constrain the latter to preserve these features.…”
Section: Related Workmentioning
confidence: 99%